Studi Etnobotani Manten Kopi sebagai Kearifan Lokal di Perkebunan Kopi Kawisari Blitar: Ethnobotanical Study of Manten Coffee as Local Wisdom in Kawisari Coffee Plantation Blitar - Aristawidya, Rifdah; Agustin, Eva Putri; Permata Sari, Dita Putri (Universitas Negeri Semarang, 2025)
Manten kopi is a traditional ritual practiced at Kawisari Plantation, Blitar, symbolizing coffee beans as a